Travelling into the other's world: South African pre-service teacher education students' construction of difference, belonging and identity - Gachago, D.; Bozalek, V.; Ng'ambi, D. (South African Journal of Higher Education, 2018)
Against the backdrop of a lack of social engagement in South Africa’s classrooms, this paper explores how nine pre-service student educators constructed stories of difference, belonging and identity in facilitated conversations around race relations in South Africa. As such it will contribute to an emerging field of research on pedagogical interventions that engage students in difficult conversations to create more socially just classrooms. Bamberg’s (2012) positioning analysis for small stories was used as analytical tool. What transpired in this analysis was that students tended to position themselves first and foremost along racial lines, revealing their experiences of continuing academic and social segregation. Although students expressed a desire to overcome these divides, they struggled to visualise a world where black and white students could engage beyond their comfort zones, moving beyond the narratives with which they grow up. Lugones’ (1987) concept of world-travelling and her suggestion that world travelling might be more difficult for those who are at most ease in their lives, was useful to unpack and understand the different roles students performed. Students’ stories also showed the importance of destabilising dominant understandings of subjectivity, by allowing the emergence of fragmented narratives in difficult conversations. Recommendations of how to use narratives to facilitate students’ world travelling include the emphasis on intersectionality, fluidity and complexity in students’ stories but also discuss the difficulties to facilitate such a process and the importance of self-reflexivity on the part of the facilitator.